Effectiveness of health education intervention based on health belief model among elderly women in Urmia, Iran - Iranagh, Jamileh Amirzadeh (2015)
Elderly population is now a challenge that affects developed and developing countries throughout the world. There is symmetry between age increase and the rise in chronic diseases. Non-communicable diseases (NCD’s) are strongly influenced by behavioural risk factors including insufficient physical activity, and unhealthy diet,which lead to elevated blood pressure, blood glucose, cholesterol levels, and body weight. So, it is essential to use physical activity and nutrition intervention program to help prevention of NCD’s. This study was aimed to evaluate the effectiveness of health education intervention based on the health belief model among elderly women in Urmia, Iran. This randomized control trial was carried out in Urmia city, which was divided to four zones and then randomly assigned to one of four groups. Then from each respective zone one primary health care centre was selected. The population sampled using a stratified, multistage probability cluster sampling design. Two hundred subjects were qualified to participate in this randomized controlled trial designed study. Subjects were randomized into four groups: (1) nutrition intervention, (2) physical activity (3) both nutrition intervention and physical activity (compound) (4) control, to either a three month education program. First outcome variables were knowledge, performance, and perception of nutrition and physical activity in the elderly women. Second outcome was determination level of fasting blood glucose, lipid profiles and anthropometric parameters before and during intervention program period. One hundred seventy two subjects with mean age 69.32 (SD=5.345), successfully completed the program duration. Among the 172 elderly women, the adherence rate to the program 82% for the nutrition group, 86% for the compound group, 86% for the physical activity group, and 90% for the control group, totalling 86% of general adherence. Generally, compared to similar intervention programs, the present study,had an acceptable level of subjects’ adherence to the program. Hence, an overall of 14% drop rate in this study showed a lower number than that in other studies. There were no significant differences in the distributions of all tests scores for the variables between the intervention and control groups prior to the intervention. At the end of the intervention, results of mixed repeated measures analysis of variance revealed a statistical significant difference in knowledge, belief, and performance of nutrition and physical activity, anthropometric parameters, lipid, and glucose between intervention groups and control group across three different measurements,after six months (p <0.001). Although, there was found significant interaction of time by group for all variable scores (p <0.001). The present study indicated that by the end of the six months intervention, the participants experienced some significant anthropometric changes. It seemed that each of the physical activity or nutrition or compound group led to improvement in the subjects’ body mass index, waist circumference, mid-upper arm circumference, and hip circumference. Without any exercise and nutrition in the control group, the participants experienced a slight increase in their anthropometric parameters. The post-intervention measurements showed significant reduction (p < 0.001) in FBS, systolic blood pressure, diastolic blood pressure in physical activity group as compared to other groups. However, comparison of result indicated that improvement in cholesterol, triglyceride, LDL, and increase in HDL in compound group were higher than nutrition alone and physical activity alone (p <0.001). This study suggests the physical activity and nutrition intervention is effective among the elderly women. Therefore, group-based nutrition and physical activity education could be an alternative solution, as it promotes favourable improvement on the conditions of the elderly with sedentary life style.